The relationship between office environment elements towards employee productivity among staff at Bahagian Pengurusan Jabatan Kesihatan Negeri Melaka / Qadariah Osman - Osman, Qadariah (Faculty of Office Management and Technology, 2015)
By conducting this research, the researcher wants to identify office environment elements towards employee productivity among staff at Bahagian Pengurusan Jabatan Kesihatan Negeri Melaka. A set of questionnaire were distributed among them to get the responds and the feedback with total respondents of 86. Besides that, a convenience sampling has been used for the finding stages and researcher also has used the Statistical Package in the Social Science Software (SPSS) version 20.0 for the process of running the data gathered and Pearson correlation analysis conducted between each elements of office environment. In general, the result of this research has showed that there is a moderate correlation between independent variables of office environment elements and dependent variable employee productivity among staff at Bahagian Pengurusan Jabatan Kesihatan Negeri Melaka. Based on that, few recommendations have been point out, which are provide adjustable desk light on the desk for each staff, make comfortable workstation for various functions, implementation by management to reduce noise level and centralize ventilation by each organization.